2020
DOI: 10.1186/s12909-020-1952-9
|View full text |Cite
|
Sign up to set email alerts
|

Medical students’ experiences with sexual discrimination and perceptions of equal opportunity: a pilot study in Germany

Abstract: Background: Data is available on sexual discrimination and subjective perceptions of equal opportunity in medical education for many countries. Surveys focussing on sexual harassment have not yet been conducted at German medical schools. Methods: A student initiative surveyed all medical students at the Hannover Medical School (MHH) using an anonymous online questionnaire on equal opportunity and sexual discrimination to identify potential problems in education. Results: A total of 343 students (15%) participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 38 publications
3
12
0
Order By: Relevance
“…We found that SH behaviors are twice as likely to be experienced by students identifying as female, consistent with multiple previous studies that female students experienced SH two to three times more often than their male peers [ 4 , 23 , 24 ]. Similar frequency for experiencing SH (most commonly 1–3 times in the past year) was reported by both sexes, suggesting that though incidents are more likely to ever occur for females, incidents are infrequent in any given year.…”
Section: Discussionsupporting
confidence: 92%
“…We found that SH behaviors are twice as likely to be experienced by students identifying as female, consistent with multiple previous studies that female students experienced SH two to three times more often than their male peers [ 4 , 23 , 24 ]. Similar frequency for experiencing SH (most commonly 1–3 times in the past year) was reported by both sexes, suggesting that though incidents are more likely to ever occur for females, incidents are infrequent in any given year.…”
Section: Discussionsupporting
confidence: 92%
“…In Germany, for example, a study based on a survey of medical students found that women who had witnessed or experienced sexual harassment during their training were more likely than women who had not to decide against pursuing surgical specialties, which typically provide among the highest pay. 35 Moreover, given the especially high rates of sexual harassment of women in male-dominated industries, job loss triggered by sexual harassment has the potential to reinforce occupational segregation, thus widening the gender pay gaps discussed in chapter 2.…”
Section: Lower Long-term Wages and Consequences For Career Trajectoriesmentioning
confidence: 99%
“…This mistreatment can have important consequences for women’s career trajectories. For example, German women medical students experience harassment three times more often than men and are thus more likely to rule out certain specialties, like surgery (Jendretzky et al 2020). Unequal treatment persists into residency, where senior women trainees in emergency medicine are evaluated more critically than men with the same level of competence, pointing to a persistent and evolving bias against women, particularly as they progress through their training, because that bias did not exist among junior trainees (Brewer et al 2020; Mueller et al 2017).…”
Section: Stratification In the Professionmentioning
confidence: 99%